Taxonomic on Aquatic Coleoptera species from Helophoridae, Hydrophilidae in Anbasa region, Al Jabal Al Akhdar -Libya - مناجي فوزي المصراتي احميده (African Journal of Advanced Pure and Applied Sciences, 2026)
This study aim to identify some species of aquatic beetles belonging to families Helophoridae and Hydrophilidae Sub Order Polyphaga, samples were collected from the Ain Anbasa reign in Aljaba Alakder, during the period from July 2023 to June 2024, by using aquatic nets randomly from the water surface ,among aquatic plants and from floating leaves the results of this study showed the recording of three species Helophorus milleri (Kuwert,1886) belonging into Helophoridae, Helochares lividus (Forster, 1771), Coelostoma hispanicum (Küster, 1848) belonging into Hydrophilidae, their identification was based on characters of the body morphology and male genitalia.